The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1460-9568.2007.05314.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional microstates within human REM sleep: first evidence from fMRI of a thalamocortical network specific for phasic REM periods

Abstract: High thalamocortical neuronal activity characterizes both, wakefulness and rapid eye movement (REM) sleep, but apparently this network fulfills other roles than processing external information during REM sleep. To investigate thalamic and cortical reactivity during human REM sleep, we used functional magnetic resonance imaging with simultaneous polysomnographic recordings while applying acoustic stimulation. Our observations indicate two distinct functional substates within general REM sleep. Acoustic stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
142
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(154 citation statements)
references
References 62 publications
(93 reference statements)
11
142
1
Order By: Relevance
“…In this line of thought, it is interesting to note that we found no signiWcant activation in the hippocampus, though both the amygdala and parahippocampal gyrus were activated. Although the reason for the inactivity of the hippocampus is not clear, this result is consistent with many recent PET (Maquet et al 1996;Braun et al 1998;Peigneux et al 2001) and fMRI (Wehrle et al 2007) studies. A second possibility is that these activations relate to the generation and maintenance of dream imagery.…”
Section: Activation Accompanying Remsupporting
confidence: 80%
See 2 more Smart Citations
“…In this line of thought, it is interesting to note that we found no signiWcant activation in the hippocampus, though both the amygdala and parahippocampal gyrus were activated. Although the reason for the inactivity of the hippocampus is not clear, this result is consistent with many recent PET (Maquet et al 1996;Braun et al 1998;Peigneux et al 2001) and fMRI (Wehrle et al 2007) studies. A second possibility is that these activations relate to the generation and maintenance of dream imagery.…”
Section: Activation Accompanying Remsupporting
confidence: 80%
“…A recent fMRI study also shows that a thalamocortical network including limbic and parahippocampal areas is speciWcally active during phasic REM periods (Wehrle et al 2007). Our present event-related fMRI study supports and extends this notion.…”
Section: Activation Accompanying Remmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, some recent fMRI studies suggest that rapid eye movements during REM sleep might be associated with increased fMRI activity in V1 (Miyauchi, Misaki, Kan, Fukunaga, & Koike, 2009). On the other hand, because several studies found that auditory stimuli may be processed to some extent during sleep (Atienza, Cantero, & Escera, 2001;Czisch et al, 2002;Perrin, Garcia-Larrea, Mauguiere, & Bastuji, 1999;Portas et al, 2000;Wehrle et al, 2007), we would predict that external auditory stimulation during sleep may effectively coordinate activation within primary and associative auditory cortices.…”
Section: Distribution Of Brain Activity During Rem Sleepmentioning
confidence: 85%
“…Several studies have shown that the temporal structure of the microstates changes as a function of the conscious/mental state of the subject, such as sleep (Wehrle et al, 2007), hypnosis (Katayama et al, 2007), centrally active medication , and mental disorders such as dementia (Strik et al, 1997), depression (Strik et al, 1995), and schizophrenia (Koenig et al, 1999;Strelets et al, 2003). In schizophrenia, a reduction in microstate duration and aberrant sequencing of the microstates has been described (Lehmann et al, 2005).…”
mentioning
confidence: 99%